Encyclopedia of Global Warming and Climate Change / GSC002260 (Thousand Oaks, Calif. : SAGE Publications, Incorporated, 2012)
Provides a multi-authored, academic yet non-technical resource to understand the importance of global warming, to appreciate the effects of human activity and greenhouse gases around the world, and to learn the history of climate change and the research enterprise examining it. The debate over the advent of global warming at least partially brought on by human enterprise has continued to ebb and flow, depending literally on the weather, politics, and media coverage of climate summits and debates. Advances in research also change the discourse as new data is collected and new scientific projects continue to explore and explain global warming and climate change. Thus, this 2nd edition updates more than half of the original entries and adds new perspectives and content
V. 1. A-E -- v. 2. F-O -- v. 3. P-Z, Index
Prev. edition published under title: Encyclopedia of global warming and climate change
Includes bibliographical references and index (volume 3)
Keywords: Global warming -- Encyclopedias; Climatic changes -- Encyclopedias; Encyclopedias